Peran Kartu Kuartet dalam Meningkatkan Motivasi Belajar Norma Siswa Sekolah Dasar - Anissa Atsilah Tsamarah; Fathurrohman (Tumoutou Social Science Journal, 2026)
Learning motivation related to normative values in elementary school student remains a challenge in Pancasila and Citizenship Education ( (PPKn). Material related to moral and ethics is often taught conventionally and abstractly, making it less able to attract students interest. This condition demands innovation in interactive and enjoyable learning media. This study aims Yo analyzer the role of quartet cards in increasing the normal learning motivation of elementary school students. The method used is a descriptive qualitative approach through a literatur review of various scientific sources, such as Journals, books, and previous research results relevant to educational Game Based Learning. The results of the study indicate that quartet cards are proven effective as an interactive learning medium that combines visual elements, competition and cooperation. This media is able to create an active, fun and meaningful learning atmosphere while increasing student participation, motivation and understanding of social and moral values. Based on these findings, it can be concluded that improving learning motivation in elementary school students requires synergy from various related parties.